Municipal energy efficiency programs as a first step towards implementing the energy management system - Mitevska M., Kuzmanovska M., Dimov Lj., (Supervisor: Lazarevska A. M.) (Факултет за електротехника и информациски технологии, Скопје (анг. Faculty of electrical engineering and information technologies ), 2017)
The results obtained from the analysis on implementing Energy Efficiency (EE) programs in 80 municipalities on the territory of the Republic of Macedonia and in the City of Skopje as a distinct unit of the local self-government, pointed at a decrease from 10-45% in annual energy consumption. Mainly, this decline is due to the implemented EE measures encompassed in the municipal Programmes for EE, such as thermal insulation of internal walls and buildings’ envelops, as well as roof and floor insulation applied to public buildings. Having in perspective that the initial analysis of the process of implementing the EE program in the Municipality of Karposh led to reduced energy consumption for 30%, this paper focuses on specific measures which contributed to this reduction and examines the potential Karposh holds to further implement a municipal Energy Management System (EnMS) in line with ISO 50001, as a continuation and extension to the already established municipal EE programs. The analysis encompasses elementary schools and kindergartens under jurisdiction of the municipality and street lighting. Being a useful tool for continuous monitoring, improvement and implementation of EE measures towards more efficient energy use and environmental protection, implementing municipal EnMS in Karposh shall further contribute to its sustainable development.
Keywords: EE, energy management, municipal energy planning